ASSESSMENT OF INTRAOCULAR PRESSURE FOLLOWING THE INTRAVITREAL INJECTION OF ANTI-VEGF - TAJWIDI, CHAKAR; TABASSUM, SHIASTA; GUL, RAHMAM (International Journal of Current Pharmaceutical Research, 2021)
Objective: The objective of the study is to assess the frequency of raised IOP after intravitreal injection of Anti VEGF by using an applanation tonometer. Methods: Each patients who fulfil the presence criteria were nominated by the researcher through ‘the outpatient department (OPD) of ophthalmology, Jinnah Post Graduate Medical Center. Performa was filled. Aim and process of study was explained to all patients. Conversant consent was reserved. Model ocular inspection, including IOP was done. By using either a 30-or 32-gauge needle, 1.25 ml bevacizumab (Avastin) were administered by the researcher under the direct supervision of consultant. Patients were consistently sterilely prepped, that was comprised incerted of topical antibiotic and anesthetic drops, supplement of a lid speculum. Later pointing the injection place on the sclera with a caliper calculating 3.0 to 3.5 mm after limbus, conjunctiva was expatriate somewhat through a sterile cotton-tipped applicator immediately earlier ingoing the eye by a needle. Later injection, place was occluded provisionally it was amended through a sterile cotton-tipped applicator while the needle remained inhibited from the eye. Since the needle was inhibited, a drop of anesthetic was employed on the cornea and IOP was measured. Then next IOP interpretation was measured later 1day of intravitreal Avastin. All pressures were measured using the applantation tonometry. IOPs were measured earlier intravitreal Avastin "baseline IOP" and instantly following injection "T0" and 1day next injection. Results: 235 Patients exactly nominated for the research study. Intravitreal Injection, Bevacizumab was applied in 235 Eyes of overstated 235 patients. Elsewhere of the 235 patients, 133 males and 102 females, Their ages ranged from 30-70 y (mean 52.02 y. The most shared sign intravitreal with bevacizumab, diabetic retinopathy observed in 114 (48.5%) patients, indicated by exudative ARMD in 70 (29.7%) patients, BRVO in 12 (5%) patients, Myopic CNV23(9.7) with CRVO observed in 11 (4.6%) patients, Eale’s sickness in 2(0.85%) patients even as Idiopathic CNV was observed in only 3 (1%) patient. Of the 235 patients, 118 (50.2%) patients with right eye suffered, 117(49.7%) patients with left eye suffered. After 24 h of intravitreal Bevacizumab Raised IOP was observed in only 3 (1.28) patient and 232(98.2) patient IOP was in the normal range. According to our study, the result of stratification with respect to age, side of the eye and gender is not significant as p-value for age (0.838), gender (0.723) and side of the eye (0.556), respectively. Conclusion: In our study, frequency of raised IOP after anti VEGF were found 3(1.28) patient out of 232 (98.2). Anti-VEGF treatment is the foundation for the management of numerous retinal illnesses. Notwithstanding its capable effectiveness in uncertain the sickness and refining, vision for the patients, intravitreal injection of anti-VEGF products may be related with overwhelming problems. To diminish the risk cautious care to the injection method and suitable post-injection observing are essential.